2015
DOI: 10.1186/s12935-016-0279-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and apoptogenic effect of hypericin, the bioactive component of Hypericum perforatum on the MCF-7 human breast cancer cell line

Abstract: BackgroundBreast cancer is the most prevalent malignancies among the women that have a high mortality. Previous studies demonstrated that hypericin, a bioactive component of Hypericum perforatum have a cytotoxic effect on the malignant cell lines. However, an anti-carcinogenic activity of hypericin on MCF-7 is uncertain. To investigate the cytotoxic effect of hypericin on MCF-7 cells, a human breast adenocarcinoma cell-line, that resistance to chemotherapy.MethodsThe MCF-7 and fibroblast (as normal cell line) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 28 publications
5
47
0
1
Order By: Relevance
“…This effect was independent from hypericins, a class of compounds peculiar of this species. In fact, not photo activated hypericin, alone, taken as reference, was not active in our model, although this subject is still under debate (Hostanska, Reichling, Bommer, Weber, & Saller, 2003;Mirmalek et al, 2016;Schwarz, Kisselev, & Roots, 2003).…”
mentioning
confidence: 81%
“…This effect was independent from hypericins, a class of compounds peculiar of this species. In fact, not photo activated hypericin, alone, taken as reference, was not active in our model, although this subject is still under debate (Hostanska, Reichling, Bommer, Weber, & Saller, 2003;Mirmalek et al, 2016;Schwarz, Kisselev, & Roots, 2003).…”
mentioning
confidence: 81%
“…Once the cell confluence was almost 80-90%, cells were subcultured and maintained. Cells were seeded in 96-or 24-well plates with the desired quantity of cells, as per the experimental protocol [42]. After 24 h, seeded cells were treated with the desired compounds and incubated for the indicated time points depending upon the different experiments.…”
Section: Cell Culturementioning
confidence: 99%
“…It has been shown that either whole extract or some biologically active constituents of different Hypericum species exhibit anti-inflammatory, anti-microbial, anti-depressant, anti-oxidant and anti-tumor activity (Bender et al, 2018;Ozkan et al, 2018;Tian et al, 2014;Zorzetto et al, 2015). Furthermore, cytotoxic, genotoxic and apoptosis-inducing effects against different cancer cells have also been highlighted in recent studies (Keskin et al, 2017;Mirmalek et al, 2015;Sarimahmut et al, 2016;Sousa et al, 2015). The most renowned Hypericum species, Hypericum perforatum (St. John's Wort), is extensively studied and utilized in traditional medicine due to its antidepressant activity and in burn-wound-healing with many pharmacological properties due to its active ingredients hypericin, hyperforin and other flavonoid compounds (Barnes et al, 2001;Baytop, 1984).…”
Section: Introductionmentioning
confidence: 96%